Archaeo-metallurgical studies of iron smelting slags from prehistoric sites in Southern Africa - H. M. Friede; A. A. Hejja; A. Koursaris (The Southern African Institute of Mining and Metallurgy, 1982)
The features of smelting slags from South African prehistoric sites and of related cinder material are described. Chemical analyses of twelve slag samples found in the Transvaal, Swaziland, and Botswana are reported and discussed. An attempt is made to establish a relationship between these slags and the ores collected at the Early Iron Age site of Broederstroom, which date between AD 350 and AD 600. The liquidus temperatures of29 slags were determined by the use oh hot-stage microscope. The major mineral phases of 16 slags were identified by X-ray diffraction and microscopic examination. It appears that the slags investigated were formed at temperatures below 1250°C or - in some cases - at temperatures only marginally in excess of 1250°C.